Get in line: Do part‐time legislatures use sunset laws to keep executive agencies in check. Issue 1 (6th October 2019) - Baugus, Brian; Bose, Feler; Jacob, Jeffry
Abstract: Sunset provisions are clauses embedded in legislation that cause a piece of legislation or a regulatory board to expire on a certain date unless the legislature takes affirmative action to renew the legislation or board. Supporters and legislators offer several reasons why sunset laws are valuable and useful. An article by Baugus and Bose (2015), reported on the king‐and‐council model of Congleton (2001), suggests that sunset laws are a key tool legislatures use in asserting themselves against an executive branch that often dominates state government. We investigate this possibility using empirical analysis, which suggests that part‐time legislatures, specifically, a form of part‐time legislature referred to as hybrid legislatures, are more prone to use sunset legislation as a tool to keep the executive preferences in check.